Outsourcing and labor taxation in dual labor markets - Koskela, Erkki; Poutvaara, Panu (Munich, 2008)
"We evaluate the effects of international outsourcing and labor taxation on wage formation and equilibrium unemployment in dual labor markets. Outsourcing promotes wage dispersion between the high-skilled and low-skilled workers. Higher domestic low-skilled wage tax, higher payroll tax and lower wage tax exemption increase optimal outsourcing. Outsourcing will reduce equilibrium unemployment of low-skilled workers both in the presence and absence of labor taxation. In the presence of outsourcing, wage tax, tax exemption and payroll tax have an ambiguous effect on equilibrium unemployment. Increasing the degree of tax progression decreases the wage rate and increases the demand of low-skilled workers. "